An unusual, new, sexually dimorphic species of Gryon Haliday (Hymenoptera: Scelionidae) from India. (2nd January 2016) - Kamalanathan, Veenakumari; Keloth, Rajmohana; Mohanraj, Prashanth; Peter, Abhilash
Abstract: Gryon ingens (Hymenoptera: Scelionidae) discovered recently in India and possessing an unusually elongate metasoma is described as a new species. With the exception of the length of the metasoma, the species characters match those of Gryon . The large and elongate eggs of the reduviid host of G. ingens sp. n. account for its unusually long habitus. The high degree of sexual dimorphism, which includes colour, encountered in this instance is atypical of this genus.